Effects of Diabetes Mellitus on Functional Outcomes and Complications After Torsional Ankle Fracture. Issue 16 (15th August 2020) - Schmidt, Tegan; Simske, Natasha M.; Audet, Megan A.; Benedick, Alex; Kim, Chang-Yeon; Vallier, Heather A.
Abstract : Introduction: It is well known that patients with diabetes mellitus experience higher complication rates after torsional ankle fracture; however, the functional consequences remain less clear. The goal of this study was to determine the effects of diabetes on complications, secondary operations, and functional outcomes after torsional ankle fracture. Methods: Nine hundred seventy-nine adult patients treated surgically for a torsional ankle injury (Orthopaedic Trauma Association 44B, 44C) over 13 years were retrospectively reviewed. Demographic information, comorbidities, injury characteristics, complications, and secondary procedures were recorded. Patient-reported outcome surveys: Foot Function Index (FFI) and Short Musculoskeletal Function Assessment were obtained after minimum of 12 months. Multivariable analysis was done to account for confounding variables. Results: One hundred thirty-one patients (13.4%) had diabetes. Diabetic patients were older (56.4 versus 43.0 years, P < 0.001), with no difference in sex or race. Body mass index was higher among diabetics (36.0 versus 30.4, P < 0.001) as were most medical comorbidities, including stroke, neuropathy, pulmonary disease, and renal disease (all P < 0.03). There were no differences in rates of dislocations or open injuries. Diabetics experienced more complications (26.0% versus 14.6%, P = 0.001), specifically deep infections (6.9% versus 1.3%, P = 0.001), and had more secondary procedures (18.3% versus 9.1%, P = 0.001), including débridement, arthrodesis, and amputation (all P < 0.02). Diabetes was a significant independent predictor of worse FFI activity limitation scores ( P = 0.032), but was not predictive of worse outcomes on any other subscore of the FFI or Short Musculoskeletal Function Assessment. Conclusions: Diabetes was associated with more complications and secondary operations. However, functional outcomes including pain and dysfunction were not markedly affected by these clinical outcomes, potentially due to diminished sensory function and less baseline physical activity among diabetic patients. Level of Evidence: Prognostic level III